Influence of continuous renal replacement therapy on the plasma concentration of tigecycline in patients with septic shock: A prospective observational study - Huang, Fang; Cao, Wen-Xiang; Yan, Yu-Ying; Mao, Tian-Tian; Wang, Xian-Wen; Huang, Dan; Qiu, Yu-Shuang; Lu, Wen-Jie; Li, Dong-Jie; Zhuang, Yu-Gang (Frontiers in Pharmacology, 2023)
Objective: The influence of continuous renal replacement therapy (CRRT) on the steady-state plasma concentration of high-dose tigecycline was investigated in septic shock patients to provide references for drug dosing. Methods: In this prospective observational study, 17 septic shock patients presenting with severe infections needing a broad-spectrum antibiotic therapy with high-dose tigecycline (100 mg per 12 h) in the intensive care unit were included and divided into CRRT group (n = 6) or non-CRRT group (n = 11). The blood samples were collected and plasma drug concentration was determined by SHIMADZU LC-20A and SHIMADZU LCMS 8040. The steady-state plasma concentration was compared between groups using unpaired t-test. Furthermore, between-groups comparisons adjusted for baseline value was also done using multivariate linear regression model. Results: Peak concentration (Cmax) of tigecycline was increased in CRRT group compared to non-CRRT group, but there were no statistical differences (505.11 ± 143.84 vs. 406.29 ± 108.00 ng/mL, p-value: 0.129). Trough concentration (Cmin) of tigecycline was significantly higher in CRRT group than in non-CRRT group, with statistical differences (287.92 ± 41.91 vs. 174.79 ± 33.15 ng/mL, p-value: 0.000, adjusted p-value: 0.000). In safety, Cmin was reported to be a useful predictor of hepatotoxicity with a cut-off of 474.8 ng/mL. In our studies, Cmin of all patients in CRRT group was lower than 474.8 ng/mL. Conclusion: The plasma concentration of tigecycline was increased in septic shock patients with CRRT treatment and only Cmin shown statistical differences. No dose adjustment seems needed in the view of hepatotoxicity. Clinical Trial Registration:https://www.chictr.org.cn/, identifier ChiCTR2000037475.